Vibrating-wire viscometry on liquid hydrocarbons at high pressure - Oliveira, Carla Padrel de (2012)
A vibrating-wire viscometer for the measurement of the viscosity of liquids at elevated pressures is described. The instrument is one of a pair, developed collaboratively in different laboratories, that operate in a relative manner according to a complete theory of the instrument. The instrument described here has been used for measurements at pressures up to 80 MPa in toluene, and in n-heptane along two isotherms.